Rancang Bangun Prototype Alat Pendeteksi Kebakaran Berbasis Sensor Gas (MQ-2): Design and Construction of a Prototype of a Sensor-Based Fire Detection Device (MQ-2) - Rachmawati Sukma; Abdul Zaid Patiran (Universitas Papua, 2025)
The prototype of an early fire detection device was designed using an MQ-2 gas sensor and an Arduino Uno microcontroller. This system is capable of recognizing the presence of smoke or flammable gas, and then automatically responds via a buzzer, water spray, LEDs, and information display on an LCD screen. Two types of smoke were used in the testing: dense smoke from burning paper and regular smoke from a cigarette, with detection distance variations ranging from 15 cm to 100 cm. Each smoke condition produced a different response according to its density level, allowing the system to differentiate between dangerous situations and provide an appropriate warning. With its simple design and affordable cost, this device has the potential to become a practical solution for fire detection systems in homes or confined spaces.